TotalTrack video intubating laryngeal mask in super-obese patients – series of cases - Gaszynski T (Dove Medical Press, 2016)
Tomasz Gaszynski Department of Emergency and Disaster Medicine, Medical University of Lodz, Lodz, Poland Background: Super-obese patients are at increased risk of difficult mask ventilation and difficult intubation. Therefore, devices that allow for simultaneous ventilation/oxygenation during attempts to visualize the entrance to the larynx, increase patient safety. TotalTrack video intubating laryngeal mask is a new device that allows for ventilation during intubation efforts. Patients and methods: Twenty-four super-obese patients (body mass index >50 kg/m2) were divided into two subgroups: intubation efforts using 1) TotalTrack and 2) Macintosh blade standard laryngoscope in induction of general anesthesia. Visualization and successful intubation was evaluated for both groups with ventilation and post-mask complications additionally evaluated for TotalTrack. Results: In all cases in the TotalTrack group, the Cormack-Lehane score was 1, ventilation and intubation was successful in 11/12 patients. No hypoxia during intubation efforts was recorded. No serious complications of use of TotalTrack were observed. In the Macintosh blade laryngoscope group, all patients were intubated, but the Cormack-Lehane score was 2 in four cases, and 3 in three cases. Conclusion: TotalTrack video intubating laryngeal mask is a device that allows for better visualization of the larynx compared to the standard Macintosh blade laryngoscope, it provides effective ventilation/oxygenation and intubation in super-obese patients. Keywords: super-obese, intubation, ventilation, laryngeal mask, standard laryngoscope, video laryngoscope